E-Newspapers Digital Deliverance?. - Marlowe Hood (IEEE spectrum)
Despite the discouraging performance of e-books in the last decade, electronic reader technology has been growing in the newspaper industry, with several newspapers in Europe and Asia already producing dedicated e-reader editions, and others following suit. While many newspapers continue to turn handsome profits, others are beginning to realize that there's not much future for the once-a-day distribution of highly perishable information printed with ink on thin sheets of expensive, chemically treated wood pulp. Aside from mobile wireless connectivity, other technologies that need to be further enhanced to ensure the e-newspaper's success include color displays and PC tablets